On precursory ULF/ELF electromagnetic signatures for the Kobe earthquake on April 12, 2013. (15th December 2015) - Schekotov, A.; Izutsu, J.; Hayakawa, M.
Highlights: ULF/ELF electromagnetic earthquake precursor to the 2013 Kobe earthquake. Magnetic field depression. Atmospheric ELF radiation. Abstract: After the 2011 Tohoku earthquake (EQ), there have been numerous aftershocks in the eastern and Pacific Ocean of Japan, but EQs are still rare in the western part of Japan. In this situation a relatively large (magnitude ( M ) ∼ 6) EQ happened on April 12 (UT), 2013 at a place close to the 1995 Kobe EQ ( M ∼ 7), so we have tried to find whether there existed any electromagnetic precursors to this EQ. Two precursory signatures are detected: one is the depression of ULF (ultra-low-frequency, 0.01–0.02 Hz) geomagnetic variations on April 9, and the second is wideband ELF (extremely low frequency) electromagnetic radiation on April 11. These results for the 2013 Kobe EQ are compared with the corresponding results for the former 1995 Kobe EQ.